2008
DOI: 10.1111/j.1467-9310.2008.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of new product development (NPD) proficiency and NPD entry strategies on product quality and risk

Abstract: This research explores the variation of new product quality and risk associated with New Product Development (NPD) entry strategies (e.g. in‐house developments and joint ventures). Our first two research questions examine the quality of new products and the variation of risk across five NPD entry strategies. Our third and fourth research questions investigate the association of the proficiency with which NPD technical activities are performed with new product quality and the risk involved in developing new pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…A well-defined, high-quality NPD process is generally recognized as a critical success factor for product success (Cooper et al, 2004;Montoya-Weiss & Calantone, 1994) and product quality (Calantone & Benedetto, 1988;Millson & Wilemon, 2008;. However, whether the use of certain technical activities and methodologies in the NPD process affects product quality positively is less clear.…”
Section: Design-for-safetymentioning
confidence: 99%
See 3 more Smart Citations
“…A well-defined, high-quality NPD process is generally recognized as a critical success factor for product success (Cooper et al, 2004;Montoya-Weiss & Calantone, 1994) and product quality (Calantone & Benedetto, 1988;Millson & Wilemon, 2008;. However, whether the use of certain technical activities and methodologies in the NPD process affects product quality positively is less clear.…”
Section: Design-for-safetymentioning
confidence: 99%
“…Design-for-Safety encompasses the NPD process and the safety management tools and methodologies used in new product development, and it has a positive causal relationship with product quality (Calantone & Benedetto, 1988;Millson & Wilemon, 2008;Song & Parry, 1997). Page 15 Safety practitioners have suggested that the issue of product safety should be addressed in parallel with the design process; however, much of the literature lacks an integrated view of product safety management methodologies and tools in the NPD process.…”
Section: H7: Concurrent Engineering Has a Positive Effect On Product mentioning
confidence: 99%
See 2 more Smart Citations
“…Proficiency and concentration on the end product and those involved, supported by learning or effectiveness of training is the way forward to learn quality management in organisational learning performance. Millson and Wilemon, (2008) hypothesised that, 'increased technical proficiency leads to increased new product quality' in new product development. This hypothesis was statistically supported by a statement which states that proficiency performance is significantly associated with new product quality (Millson & Wilemon, 2008).…”
Section: Quality Management Through Proficiency Concentration and Efmentioning
confidence: 99%